2015
DOI: 10.1016/j.amjcard.2015.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Long-Term Risks of Ischemic and Bleeding Complications After Percutaneous Coronary Intervention With Drug-Eluting Stents

Abstract: Introduction-While trials comparing antiplatelet strategies after coronary intervention report average risks of bleeding and ischemia in a population, there is limited information to guide choices based on individual patient risks, particularly beyond one year after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 39 publications
4
25
2
2
Order By: Relevance
“…19 Prior studies have demonstrated that smoking is associated with worse clinical outcomes following stent placement in other locations as well. In a study of Ͼ9000 patients undergoing percutaneous coronary intervention with drug-eluting stents, Matteau et al 20 found that smoking was an independent risk factor for postoperative ischemic events and bleeding. Similar to patients with PEDs, patients with percutaneous coronary intervention are required to receive dual antiplatelet therapy following their intervention.…”
Section: Discussionmentioning
confidence: 99%
“…19 Prior studies have demonstrated that smoking is associated with worse clinical outcomes following stent placement in other locations as well. In a study of Ͼ9000 patients undergoing percutaneous coronary intervention with drug-eluting stents, Matteau et al 20 found that smoking was an independent risk factor for postoperative ischemic events and bleeding. Similar to patients with PEDs, patients with percutaneous coronary intervention are required to receive dual antiplatelet therapy following their intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Можно также по-лагать, что у большинства больных ожидаемая вероят-ность ТО существенно превосходит вероятность кровоте-чений. В пользу данного предположения свидетельствуют анализ популяций PROTECT и PROTECT US, объеди-нивший 9727 больных, которые подвергались ЧКВ и на-блюдались на протяжении 4 лет [26]. Определенные на основании многофакторного анализа предикторы ТО и ГО оказались тесно связаны между собой.…”
Section: оценка риска развития тромботических осложнений у больных ибunclassified
“…Unfortunately, the information to recommend choices based on individual patient risks is scarce, especially beyond 1 year of DES placement and DAPT. There are many common risk factors associated with individual patient risks of ischemia and bleeding[47]. …”
Section: Antiplatelet Medicationmentioning
confidence: 99%
“…Two large studies, the Patient Related Outcomes With Endeavor vs Cypher Stenting Trial (PROTECT), and PROTECT US, determined that at a median follow-up of 4.1 years, major bleeding occurred in 2.8% subjects and ischemic events in 6.3%[47]. There was no difference in mortality or stroke[56].…”
Section: Antiplatelet Medicationmentioning
confidence: 99%